‘Performance: Encarna-acciones de la contemporaneidad’, Facultad de Artes, Universidad de Antioquia - Chaverra Brand, Angela María (Latin American Theatre Review, 2013)
Since 2003, the project “El Cuerpo Habla” has looked into the question of happenings of the flesh in the city of Medellín and how the paradigm change that occurred with the appearance of the vanguards in the 20th century has given rise to the expansion of concepts such as representation, resistance, and fabulation, all of which allow us to sketch out new strategies in the construction of artistic tendencies in which different techniques and awarenesses such as in performance, permanent artistic workshops, internal and interdisciplinary dialogues, and pedagogical proposals are integrated with those that take on board art, the relation of self, other, and the environment and that are open to multiplicity, divergence, and variation.